Genetic Effects Influence Grouping Behavior in Beetles - Sharp, Haelea; Marshall, Jeremy (My University, 2018)
We studied the behavioral patterns of Red Flour Beetles. They are a common pest of stored grain products. This experiment tested the grouping behavior of two strains of Red Flour Beetle to see if observed grouping behavior could have a genetic or environmental influence. We hypothesized that if different strains were closely associated for two weeks their environment would encourage them to demonstrate grouping behavior together. When observing the specimens we could not confirm the hypothesis. Beetles of the same line tended to group together while unrelated individuals did not tend to associate even after two weeks in the same jar. For these two strains, an environmental effect on grouping is not supported. This could potentially be used in further research on effective control methods and how to tailor them to specific strains.
Keywords: Fall 2018